1996
DOI: 10.1136/bmj.313.7048.36
|View full text |Cite|
|
Sign up to set email alerts
|

Trials to assess equivalence: the importance of rigorous methods

Abstract: The aim of an equivalence trial is to show the therapeutic equivalence of two treatments, usually a new drug under development and an existing drug for the same disease used as a standard active comparator. Unfortunately the principles that govern the design, conduct, and analysis of equivalence trials are not as well understood as they should be. Consequently such trials often include too few patients or have intrinsic design biases which tend towards the conclusion of no difference. In addition the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
640
2
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 964 publications
(655 citation statements)
references
References 10 publications
6
640
2
7
Order By: Relevance
“…The present study, powered to rule out a 0.67 hazard ratio of death with the weekly schedule, suggests survival be very similar with the two compared schedules (HR of death 1.04), although, of course, interpretation of data in terms of equivalence (Jones et al, 1996) is not allowed.…”
Section: Discussionmentioning
confidence: 69%
“…The present study, powered to rule out a 0.67 hazard ratio of death with the weekly schedule, suggests survival be very similar with the two compared schedules (HR of death 1.04), although, of course, interpretation of data in terms of equivalence (Jones et al, 1996) is not allowed.…”
Section: Discussionmentioning
confidence: 69%
“…As this was an equivalence trial, a confidence interval (CI) approach was used (Jones et al, 1996). The difference in outcomes was calculated, adjusting for differences in baseline scores using multiple linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…For each outcome, the 95% CIs around the difference were calculated. An outcome was considered 'equivalent' when the 95% CI for the difference between the intervention and control group fell completely within a predetermined equivalence limit (Jones et al, 1996). Where the 95% CI for the observed difference fell completely outside the equivalence limit, we considered the outcomes would be 'nonequivalent'.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation (see (Meuldijk et al, 2012) indicated that 500 patients (alpha=0·05, 1 -β=0·80, two-sided) were required to demonstrate equivalence (Jones et al, 1996). Concise care will be deemed equivalent to standard care, if the 95% confidence interval (CI) for the observed difference in the proportions of treatment success (defined as a 50% reduction in BSI score compared to baseline BSI score) do not cross these predefined clinical margins of equivalence (∆) of -15% and + 15% including an acceptable difference of 5% (Meuldijk et al, 2012;Wiens, 2002;Jones et al, 1996).…”
Section: Equivalence Marginsmentioning
confidence: 99%
“…Concise care will be deemed equivalent to standard care, if the 95% confidence interval (CI) for the observed difference in the proportions of treatment success (defined as a 50% reduction in BSI score compared to baseline BSI score) do not cross these predefined clinical margins of equivalence (∆) of -15% and + 15% including an acceptable difference of 5% (Meuldijk et al, 2012;Wiens, 2002;Jones et al, 1996). The equivalence margins are specified a priori on the basis of a clinical notion of detection, a minimally clinically important difference in effect (see Meuldijk et al2012).…”
Section: Equivalence Marginsmentioning
confidence: 99%